PENGARUH KONSUMSI, INFLASI, DAN KURS USD TERHADAP VOLUME IMPOR SUSU SAPI - Setyawan, Putu Dendy Ananda; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Milk is a food requirement that has a very large role for the health of the body because of its protein and amino acid content. The lack of domestic milk production has forced the government to implement an import policy to fill the shortage of production. Many things affect imports, so it is necessary to identify what factors can affect milk imports in Indonesia. This study aims to analyze the effect of consumption, inflation and the USD exchange rate simultaneously and partially on the volume of imports of Indonesian cow's milk and to determine the most dominant variable influencing the volume of imports of Indonesian cow's milk. The analysis technique used in this research is multiple linear regression. The results of this study found that the variables of consumption, inflation, and the USD exchange rate had a significant effect on the volume of imports of Indonesian cow's milk. Partially, consumption and inflation have a positive and significant effect on the volume of imports of Indonesian cow's milk, while the USD exchange rate partially has a negative and significant effect on the volume of imports of Indonesian cow's milk. Consumption variables have a dominant effect on the volume of imports of Indonesian cow's milk Keywords : imports of cow's milk, consumption, inflation, and the exchange rate Klasifikasi JEL: C68, F43, L52